Women’s Career Decision Making and Interest in Engineering - Concetta Tino; Maria Cristina Lavagnolo; Monica Fedeli; Laura Bierema (AS: Andragoška Spoznanja)
The aim of the paper was to better understand the influence of personal and contextual factors on women’s career decision making and interest in undergraduate engineering students. On the basis of Social Cognitive Career Theory and utilising a qualitative approach, nine interviews were conducted with women undergraduates at a university in Northern Italy. The results reveal four major aspects: a) the women’s interest in engineering is cultivated by different contextual factors in the same way across multiple cultures; b) self-efficacy affects their interest in engineering; c) this interest is nurtured by internal and external recognition; d) their career decision making is determined by an interdependence of personal and contextual factors. The paper contributes to promoting cultural changes in engineering fields. Some practical implications for education professionals and policy makers were also reported.